Vulnerability assessment of Surigao Metro Water District under seismic hazard - Better, Sheena I. (Animo Repository, 2018)
Earlier this year, Surigao Del Norte, a province in the Philippines experienced a 6.7 magnitude earthquake. The severe ground movement caused some of the buried pipelines to be pulled-out from their supports. This type of failure occurs when the ground strain during extreme seismic excitation exceeds the strain capacity of the buried pipe. The failure of the pipes resulted in the loss of water that was vital for post-earthquake recovery efforts. In this regard, there is a need to re-assess the vulnerability of the buried pipes of the water network. In this paper, a probabilistic seismic hazard analysis (PSHA) was employed to estimate the seismic hazard within the concession area. Past seismic data that can significantly affect the target structure is used for this purpose. The buried water lifeline system of Surigao Metro Water District (SMWD) was chosen as the target lifeline. An appropriate ground motion prediction equation (GMPE) was used to develop the uniform hazard response spectra for the site. To assess the vulnerability of the pipes three damage states were considered: major, moderate and minor. The probability of major, moderate and minor damage to each pipe was determined using Monte Carlo simulation. Subsequently, fragility curves were obtained.